Latent Securitisation of Illegal, Unreported and Unregulated (IUU) Fishing in Indonesia - Taufika, Rage (Global: Jurnal Politik Internasional, 2020)
This paper aims to explore and explain to what extent and in what ways the Indonesian Government has securitised the Illegal, Unreported and Unregulated (IUU) fishing in Indonesia since 2009, by utilising critical discourse analysis. Using the Securitisation theory from the Copenhagen School, this paper explains the analysis of the speech act and extraordinary measures from SBY’s administration, Jokowi’s first term and second term administration. While IUU fishing has been a severe global issue, 30 percent of the cases take place in Indonesia and it becomes a serious threat for the economy and maritime resources. In 2009, Indonesia amended the fisheries law by establishing the new article about the right to burn and sink illegal foreign vessels. However, the securitisation remained ‘latent’ as it lacks the extraordinary measures and supporting speech act from the government. In 2014, during Jokowi’s first term, Indonesia had done extraordinary measures by regularly sinking the illegal foreign vessels. During Jokowi’s second term, the measures were gone, although the law still exists. Thus, it became ‘latent’ again in 2019 up until present. This paper claims that the Indonesian Government successfully securitised the issue in 2014 after the latent securitisation that happened in 2009. However, it remained ‘latent’ again in 2019 up until now.